2019
DOI: 10.1158/2159-8290.cd-17-1152
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Informed Targeted Therapy for Osteosarcoma

Abstract: Osteosarcoma is a highly aggressive cancer for which treatment has remained essentially unchanged for more than 30 years. Osteosarcoma is characterized by widespread and recurrent somatic copy-number alterations (SCNA) and structural rearrangements. In contrast, few recurrent point mutations in protein-coding genes have been identifi ed, suggesting that genes within SCNAs are key oncogenic drivers in this disease. SCNAs and structural rearrangements are highly heterogeneous across osteosarcoma cases, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
289
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(319 citation statements)
references
References 76 publications
11
289
2
Order By: Relevance
“…Tp53 was first reported to hold intron 1 rearrangement by Masyda et al (Masuda et al, 1987). A series of studies verified the presence of the mutation in TP53 in OS (Chen et al, 2014;Ribi et al, 2015;Sayles et al, 2019). In this study, we found that expression of TP53 was inhibited after overexpression of miRNA-1972, while TP53 expression was enhanced after overexpression of the lncRNA LINC00588 at the protein level.…”
Section: Discussionsupporting
confidence: 63%
“…Tp53 was first reported to hold intron 1 rearrangement by Masyda et al (Masuda et al, 1987). A series of studies verified the presence of the mutation in TP53 in OS (Chen et al, 2014;Ribi et al, 2015;Sayles et al, 2019). In this study, we found that expression of TP53 was inhibited after overexpression of miRNA-1972, while TP53 expression was enhanced after overexpression of the lncRNA LINC00588 at the protein level.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies, including a large meta-analysis, have associated specific genetic TP53 alterations with survival in patients with OS, 11 suggesting mutation-specific phenotypes. 13 These patterns, however, explain only a small number of events, and the degree of cell-to-cell heterogeneity within a tumor remains unknown, though chromosomal heterogeneity could establish mechanisms for diversity that would facilitate adaptation to cellular stresses, such as chemotherapy. 9 Beyond this small set of mutations, the most common characteristic of OS is structural complexity through chromosomal rearrangements, copy number variation, kataegis, and chromothripsis, which occur broadly throughout the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent work has shown that a limited set of copy number patterns can group OS tumors into subtypes that may predict response to certain targeted agents. 13 These patterns, however, explain only a small number of events, and the degree of cell-to-cell heterogeneity within a tumor remains unknown, though chromosomal heterogeneity could establish mechanisms for diversity that would facilitate adaptation to cellular stresses, such as chemotherapy. Surprisingly, OS lacks common or recurrent changes in DNA repair pathway genes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it should be acknowledged that a randomized study focusing on this topic is not feasible. Personalized approaches such as those based on patient‐derived xenografts, immunotherapy, and a genome‐informed strategy might represent an opportunity for these patients in the future . Currently, an individualized treatment should be performed; at the same time, it is important to inform patients with LR from osteosarcoma that, at present, in case of surgical complete remission, no evidence of clinical benefit from second‐line chemotherapy is available.…”
Section: Discussionmentioning
confidence: 99%